Тафономия пещерных местонахождений ископаемых позвоночных - Рідуш, Богдан (My University, 2013)
Taphonomic features of the caves are crucial for the formation inside of the specific deposits containing paleogeographical records. We have improved the taphonomic classification of the cave type localities of fossil vertebrates, distinguishing it subtypes: zoogenic, gravigenic, anthropogenic and redepositional (secondary), and their corresponding individual faces and groups of faces.